Learn API Testing 2022
DOI: 10.1007/978-1-4842-8142-0_11
|View full text |Cite
|
Sign up to set email alerts
|

API Documentation

Abstract: In this study, we address the issue of API hallucinations in various software engineering contexts. We introduce CloudAPIBench, a new benchmark designed to measure API hallucination occurrences. CloudAPIBench also provides annotations for frequencies of API occurrences in the public domain, allowing us to study API hallucinations at various frequency levels. Our findings reveal that Code LLMs struggle with low frequency APIs: for e.g., GPT-4o achieves only 38.58% valid low frequency API invocations. We demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The former is a surface on which one can draw using DrawingContext class. This class contains Draw-Line method suitable for the purpose of signal plotting [6]. This method is simple from the developer point of view, however, fl exibility is lower comparing to WriteableBitmap.…”
Section: Drawingvisual Methodsmentioning
confidence: 99%
“…The former is a surface on which one can draw using DrawingContext class. This class contains Draw-Line method suitable for the purpose of signal plotting [6]. This method is simple from the developer point of view, however, fl exibility is lower comparing to WriteableBitmap.…”
Section: Drawingvisual Methodsmentioning
confidence: 99%
“…The NHS platform provides an application programming interface (API) that allows access to the patient ratings and reviews [20]. A custom web scraper was built for the project using the NHS API to collect the patient ratings and reviews.…”
Section: Nhs Patient Feedbackmentioning
confidence: 99%
“…We have found that HC1 and HC2 both are using Light Gradient Boost (LGB) model for prediction. The code for building the two models are: inversely proportional to the frequency of the class [25,43]. In this case, HC1 mitigates the male-female imbalance in its prediction.…”
Section: Analyze Fairness Of the Modelsmentioning
confidence: 99%
“…We have observed that class_weight hyperparameter in LGBMClassifier allows developers to control group fairness directly. However, the library documentation of LGB classifier suggests that this parameter is used for improving performance of the models [43,47]. Though the library documentation mentions about probability calibration of classes to boost the prediction performance using this parameter, however, there is no suggestion regarding the effect on the bias introduced due to the wrong choice of this parameter.…”
Section: Analyze Fairness Of the Modelsmentioning
confidence: 99%